Investigasi Kinerja Relai Proteksi Saluran Transmisi dengan Kompensator Seri - Nanang Rohadi; Nendi Suhendi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2023)
This paper aims to investigate the measurement results of closed loop fault impedance using conventional distance relay algorithms (SEL-421 distance relay) when used as protective tools on transmission lines with series compensators and several uncertainty parameters (factors). Several system’s factors can emerge concurrently, and the series compensators may affect the relay algorithm’s performance, particularly on the phase fault to ground. However, the existing testing method of the relay performance only alters one factor while simultaneously keeping others constant. This technique is no longer relevant when several factors are not considered simultaneously, affecting the relay performance during faults. For algorithm investigations as in actual conditions, several fault scenarios were performed at the fault point before and after series compensators while simultaneously changing the values of several factors in the system model through fault simulations. This research employed the DIgSILENT PowerFactory for power system modeling and fault simulation. In fault testing simulations, Thevenin equivalent circuit with two sources and 42% series compensator were placed in the center of a 300 km of a 400 kV transmission line. Several fault scenarios and the fault impedance measurement as a function of changes in several factor values were performed automatically. An automated testing simulation was developed using the DIgSILENT Programming Language (DPL) to read data samples generated through the SIMLAB software for several factors. A series compensator affected the performance of the relay algorithm for calculating the fault impedance when faults occurred after the compensator. For faults after the compensator, changing several factors simultaneously affects the relay’s accuracy and aggravates the relay’s performance, specifically relay operation failure in the form of underreaching and overreaching. The developed testing technique is expected to be utilized as a cutting-edge testing tool for the development and implementation of relays in a timely manner and as in actual conditions.